Crack configuration feature and fracture surface difference for high pressure die casting hypereutectic Al-Si alloys in high cycle fatigue. (December 2021) - Wang, J.; Jiao, X.Y.; Xie, H.L; Deng, B.; Xiong, S.M.
Highlights: Flat propagation zone in fatigue surface differed with Si content. Microvascular network analyses were used in crack analyses. Crack propagation behavior was measured according to thickness and length. Crack configuration feature was analyzed statistically. Stress simulation and microstructural distribution explained the crack propagation difference. Abstract: Fatigue crack surfaces for three high pressure die casting hypereutectic Al-Si alloy plates were characterized by synchrotron X-ray tomography and CT technology. Focused on the retained pores, microvascular network analyses offered an innovative method to obtain crack configuration feature and analyze the crack propagation behavior in low ductility hypereutectic alloys which in-situ experiments were hard to achieve. With more Si content, the crack local thickness difference along the crack propagation path was more obvious and laid the foundation for more local tortuous morphology. With less Si content, the crack size was tapered and more branches occurred as a way to elongate the crack length. As rigid phases in the microstructure, primary silicon particles worked as obstacle for the whole crack propagation and their volume content agreed with the overall crack fluctuation. Therefore, the difference of flat propagation surface in three alloys was explained by crack configuration difference and crack deflection based on PSPs obstacle effect.